Escherichia coli Nissle 1917 bacterial ghosts retain crucial surface properties and express chlamydial antigen: an imaging study of a delivery system for the ocular surface - Montanaro J; Inic-Kanada A; Ladurner A; Stein E; Belij S; Bintner N; Schlacher S; Schuerer N; Mayr UB; Lubitz W; Leisch N; Barisani-Asenbauer T (Dove Medical Press, 2015)
Jacqueline Montanaro,1 Aleksandra Inic-Kanada,1 Angela Ladurner,1 Elisabeth Stein,1 Sandra Belij,1 Nora Bintner,1 Simone Schlacher,1 Nadine Schuerer,1 Ulrike Beate Mayr,2 Werner Lubitz,2 Nikolaus Leisch,3 Talin Barisani-Asenbauer11Laura Bassi Centres of Expertise, OCUVAC – Centre of Ocular Inflammation and Infection, Centre for Pathophysiology, Infectiology, and Immunology, Medical University of Vienna, Vienna, Austria; 2BIRD-C GmbH & Co KG, Kritzendorf, Austria; 3Department of Ecogenomics and Systems Biology, University of Vienna, Vienna, AustriaAbstract: To target chronic inflammatory ocular surface diseases, a drug delivery platform is needed that is safe, possesses immunomodulatory properties, and can be used either for drug delivery, or as a foreign antigen carrier. A new therapeutic approach that we have previously proposed uses nonliving bacterial ghosts (BGs) as a carrier-delivery system which can be engineered to carry foreign antigens and/or be loaded with therapeutic drugs. The parent strain chosen for development of our BG delivery system is the probiotic Escherichia coli strain Nissle 1917 (EcN), whose intrinsic properties trigger the innate immune system with the flagella and fimbriae used to attach and stimulate epithelial cells. In previous studies, we have shown that EcN BGs are safe for the ocular surface route, but evidence that EcN BGs retain flagella and fimbriae after transformation, has never been visually confirmed. In this study, we used different visualization techniques to determine whether flagella and fimbriae are retained on EcN BGs engineered either for drug delivery or as a foreign antigen carrier. We have also shown by immunoelectron microscopy that EcN retains two foreign antigens after processing to become EcN BGs. Furthermore, we demonstrated that BGs derived from EcN and expressing a foreign antigen attachment to conjunctival epithelial cells in vitro without causing reduced cell viability. These results are an important step in constructing a delivery system based on a nonliving probiotic that is suitable for use in ocular surface diseases pairing immunomodulation and targeted delivery.Keywords: delivery system, flagella, fimbriae, foreign antigen, electron microscopy, epithelial cells